The CO2 absorption spectrum in the 2.3 µm transparency window by high sensitivity CRDS: (I) Rovibrational lines. (November 2016) - Vasilchenko, S.; Konefal, M.; Mondelain, D.; Kassi, S.; Čermák, P.; Tashkun, S.A.; Perevalov, V.I.; Campargue, A.
Abstract: The absorption of carbon dioxide is very weak near 2.3 µm which makes this transparency window of particular interest for the study of Venus' lower atmosphere. As a consequence of the weakness of the transitions located in this region, previous experimental data are very scarce and spectroscopic databases provide calculated line lists which should be tested and validated by experiment. In this work, we use the Cavity Ring Down Spectroscopy (CRDS) technique for a high sensitivity characterization of the CO2 absorption spectrum in two spectral intervals of the 2.3 µm window: 4248–4257 and 4295–4380 cm −1 which were accessed using a Distributed Feed Back (DFB) diode laser and a Vertical External Cavity Surface Emitting Laser (VECSEL) as light sources, respectively. The achieved sensitivity (noise equivalent absorption, α min, on the order of 5×10 −10 cm −1 ) allowed detecting numerous new transitions with intensity values down to 5×10 −30 cm/molecule. The rovibrational assignments were performed by comparison with available theoretical line lists in particular those obtained at IAO Tomsk using the global effective operator approach. Hot bands of the main isotopologue and 16 O 12 C 18 O bands were found to be missing in the HITRAN database while they contribute importantly to the absorption in the region. Additional CRDS spectra of a CO2 sample highly enriched in 18 O were recorded in order to improve the spectroscopy of this isotopologue. As a result about 700 lines of 16 O 12 C 18 O, 16 O 12 C 17 O, 17 O 12 C 18 O, 12 C 18 O2 and 13 C 18 O2 were newly measured. The status of the different databases (HITRAN, CDSD, variational calculations) in the important 2.3 µm transparency window is discussed. Possible improvements to correct evidenced deficiencies are suggested. Highlights: High sensitivity CRDS with a VECSEL in the 2.3 µm transparency window of CO2 . Natural and 18 O enriched CO2 spectra recorded with unprecedented sensitivity. Experimental test of the spectroscopic databases of CO2 (HITRAN, CDSD, variational ). Relatively strong bands missing in HITRAN and CDSD line lists. Illustration of the high quality intensities and completeness of the Ames database.